(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Cytotoxic and genotoxic effects of methanolic extract of the roots of Strobilanthes heyneanus Nees have been studied on the root meristem cells of Allium cepa. Roots of A. cepa were exposed to different concentrations (0.01%, 0.05%, 0.1% and 0.5%) of the extract for ½, 1, 2 and 3 h. Mitotic index and chromosomal aberrations in the treated cells were analysed. Distilled water has been used as control. Mitotic index val¬ues were decreased with increasing concentrations and longer treatment durations compared to the control (p < 0.05) in dose and time dependent manner. Additionally, different abnormal mitotic figures were observed in all treatments. Among these abnormalities were nuclear and chromosome lesions, anaphase bridges, C-mitosis, pulverization, stathmo-anaphases, diagonal orientation, chromosome fragments etc. The total percentage of aberrations generally increased with increasing concentrations of the extract and longer durations of exposure. The observations of the present study are a clear indication of clastogenic and non-clastogenic property of the extract, which is evident from the direct actions on the chromosomes and manifestation of spindle abnormalities.